INTEGRASI WAHDATUL ULUM DENGAN PENDEKATAN TRANSDISIPLINER SERTA RELEVANSINYA DALAM FILSAFAT ISLAM - Sirait, Azyana Alda; Salminawati, Salminawati; Abdullah, Radhinal; Febrian, M Agil (Reflektika, 2023)
This article discusses the Integration of Wahdatul Ulum with a Transdisciplinary Approach and its Relevance in Islamic Philosophy. The research employs the library research method with a content analysis approach. The primary data source is Syahrin Harahap's book on Wahdatul Ulum, supported by relevant secondary research. Data collection instruments involve identifying theoretical sources, searching for references, source selection, and analysis and interpretation.The research findings indicate that Wahdatul Ulum is an effort to integrate religious knowledge with general knowledge, while transdisciplinarity seeks to create new theories by building relationships across various fields of knowledge. This concept emerges as a solution to unite science and religion in addressing diverse challenges in both intellectual and spiritual aspects. This integration represents a significant step in comprehending and addressing the complexity of the relationship between science and religion in the context of Islamic Philosophy.